Working by hindsight: a mixed-method process evaluation of the Norwegian ACTNOW RCT with recommendations for university-practitioner partnerships and early childhood educator professional development - Wiles, Bradford Broyhill (My University, 2026)
This thesis presents a mixed-method process evaluation of the ACTNOW randomized controlled trial (RCT), which aimed to enhance early childhood educator professional development through university-practitioner partnerships (UPPs) in Norway. The ACTNOW project focused on promoting physical activity (PA) in preschools via a collaborative model involving pracademics (i.e., academics engaged in practical problem solving) and preschool staff. The intervention included a seven-month professional development program supported by digital resources, on-site visits, and ongoing support. Quantitative data from surveys and qualitative data from interviews and focus groups revealed high levels of practitioner engagement, perceived improvements in children’s PA, motor skills, and cognitive development, and staff integration of ACTNOW practices into daily routines. Key findings highlighted the importance of policy alignment, relational trust, and flexible intervention design. Practitioners valued the co-creation process and reported immediate, visible outcomes reinforcing their commitment to the work. The study underscores the role of pracademics in fostering responsive, context-sensitive partnerships and suggests that UPPs can serve as infrastructures for sustained pedagogical transformation. Limitations include potential recall and social desirability biases, and the specificity of the Norwegian context. Future research should explore mechanism activation across diverse settings using realist or other evaluation frameworks along with organizational theories. Overall, ACTNOW demonstrates that well-designed UPPs can bridge research and practice, empower educators, and promote sustainable change in early childhood education.
Keywords: Physical activity; Early childhood education; University partnerships; Norway; Readiness for change